Pengaruh Ukuran Perusahaan dan Working Capital Turnover terhadap Profitabilitas pada PT Unilever Tbk Tahun 2014-2023 - Rosalia Indah Ariani; Mirza Anindya Pangestika (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
This study purpose to analyze the Effect of Company Size and Working Capital Turnover (WCT) on Profitability (ROA) at PT Unilever Indonesia Tbk in 2014-2023. This study uses a quantitative method. The population and sample in this study are the Quarterly Financial Reports of PT Unilever Indonesia Tbk in 2014-2023. The sample in the study was 40 financial reports taken using saturated sampling techniques. The data analysis used in this study is multiple linear regression analysis using the SPSS 22 application. The results of the study indicate that partially the Working Capital Turnover (WCT) variable has an effect on Profitability (ROA). While the company size variable partially has no effect on Profitability (ROA). Simultaneously, the company size and Working Capital Turnover (WCT) variables have an effect on Profitability (ROA) with a determination coefficient value of 16.1%.